KEADILAN BAGI ISTRI AKIBAT PUTUSAN BATAL DEMI HUKUM - Supraptiningsih, Umi (Indonesian Association of Islamic Family Law Lecturers, 2019)
Marriage is carried out in order to create a happy and eternal family according to based on the hand of God. However, sometimes divorce must be exist as it was desired by the husband. Accordingly, he submitted a plea of divorce to the Religious Court to obtain an aproval. As he obtained the aproval from Religious court to divorce his wife, the husband disobeyed the court orders until the time limit was expired. Of course, it lead to the injustice gained by the wife. Accordingly, the current research focused on three aspects, namely (1) the legal consequences of verdict with no pronouncing of a divorce pledge. (2) The marital status of both the husband and the wife as the jurisprudence has been void and (3) The justice for the wife because the verdict has been expired due to disobedience carried out by the husband. Normative research with case study design was accomplished in this study. The finding revealed that the verdict with no statement of divorce pledge carried out by the husband before the deadline will not bring about effects for both the claiment (husband) or the defendant (wife). In other word, the marital status did not change as they were still legally married. In line with justice, the wife was aggrieved by the husband, and she did not gain justice either on her marital status, rights and legal certainty.